Ganti Rugi Penyewa Atas Pemanfaatan Fasilitas Kamar Hotel Menurut Fatwa DSN-MUI NO: 112/DSN-MUI/IX/2017 (Studi Kasus Hotel Syariah Kec. Rantau Utara Kab. Labuhan Batu) - Hasibuan, Eliza Hanum; Zahara, Fatimah (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
This research is entitled tenant compensation for the use of hotel room facilitiesaccording to the DSN-MUI fatwa NO: 112/DSN-MUI/IX/2017 (Case study ofsharia hotels in North Rantau District, Labuhan Batu Regency), this study aimsto find out how the provisions for compensation the tenant's loss for the use ofhotel room facilities, how is the implementation of compensation for the tenantfor the use of hotel room facilities according to the DSN-MUI fatwa NO:112/DSN-MUI/IX/2017 in Rantau Utara District, including, Wisma Syariah Hotel,Ahza Syariah and Rifana Residence Syariah. This research uses field research.The research method used is a qualitative research method and data sources wereobtained through interviews with 3 tenants (Musta'jr) and 3 lessees (Mu'jir). Theresults of this study indicate that there are still hotels that enforce compensationlaws for the use of room facilities, this clearly violates the rules according to theFatwa of the National Syari'ah Council Number 112/DSN-MUI/IX/2017concerning Ijarah Contracts which states that Musta'jir in ijarah contract 'ala ala'yan, is not obliged to bear the risk of losses arising from utilization, except foral -ta'addi, al -taqshir, or mukhalafat al-syuruth, and violates the contents andterms of the contract. So that the implementation of leasing creates harm or directimpacts such as a party who is harmed where this contains dharar and includestyrannical actions against tenants.